Determinan Nilai Perusahaan Dengan Kinerja Keuangan Sebagai Variabel Intervening - Tri Neliana; Rina Destiana (JAS (Jurnal Akuntansi Syariah))
This study aims to show the effect of institutional ownership, audit committee size, and corporate social responsibility (CSR) on firm value with financial performance as the intervening variable. This study uses quantitative methods with secondary data sources in company annual reports. The population of this study is manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2020 period. The sampling technique used purposive sampling to obtain a sample of 74 companies. The data analysis technique used path analysis. The results showed that financial performance had a positive and significant effect on firm value. Institutional ownership and size of the audit committee do not affect financial performance. Meanwhile, CSR has a positive and significant effect on financial performance. Institutional ownership and the size of the audit committee have a positive and significant effect on firm value. At the same time, CSR does not affect the company's value. Institutional ownership does not affect firm value through financial performance. At the same time, the size of the audit committee and CSR affects the company's value through financial performance. This study can reference company management and investors in developing companies and investing.